2006
DOI: 10.1007/s10706-006-9106-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the water balance of two soil cover systems

Abstract: Soil cover systems are widely used for containment of municipal solid waste, hazardous and mine waste, with the objective of limiting the ingress of precipitation and oxygen. The ability to predict their long-term performance is crucial, as their failure would result in the release of contaminants to the environment. However, monitoring covers over the long term to derive the information needed to aid in design is impractical and there are no large-scale covers that have been in use for a long enough period to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…However, for the traditional non-hysteretic model (NHM), only one branch of the major hysteresis SWCC loop is used, generally the main drying branch due to its relatively easy measurement (Adu-Wusu et al 2007;Yanful et al 2006). There are also cases where both main drying and main wetting SWCC branches are used to simulate the drying and wetting boundary conditions respectively, while ignoring the transition process in between and artificially switching the hydraulic state in the whole soils from drying to wetting, or vice versa (Tami et al 2004;Indrawan et al 2007).…”
Section: Formulation Of Hysteretic Hydraulic Modelmentioning
confidence: 99%
“…However, for the traditional non-hysteretic model (NHM), only one branch of the major hysteresis SWCC loop is used, generally the main drying branch due to its relatively easy measurement (Adu-Wusu et al 2007;Yanful et al 2006). There are also cases where both main drying and main wetting SWCC branches are used to simulate the drying and wetting boundary conditions respectively, while ignoring the transition process in between and artificially switching the hydraulic state in the whole soils from drying to wetting, or vice versa (Tami et al 2004;Indrawan et al 2007).…”
Section: Formulation Of Hysteretic Hydraulic Modelmentioning
confidence: 99%
“…Berechnungen von Khire et al zum Wasserhaushalt von mineralischen Deponieoberflächenabdichtungen ergaben eine tendenzielle Überschätzung des Sickerwassers durch die abdichtende Schicht, obgleich zu den Materialien labortechnisch ermittelte hydraulische Kennwerte vorlagen. Adu‐Wusu et al belegten mit Berechnungen von Lysimetern in einer Deponieoberflächenabdichtung die Bedeutung einer zutreffenden Abbildung der hydraulischen Eigenschaften der Böden. So zeigten sie die Notwendigkeit einer Kalibrierung der Saugspannungs‐Wassergehalts‐Beziehungen und der ungesättigten hydraulischen Leitfähigkeit der betrachteten Böden anhand gemessener Sickerwassermengen, um realistische Prognoseergebnisse mittels numerischer Berechnungen erzielen zu können.…”
Section: Introductionunclassified
“…Untersuchungen von Adu‐Wusu et al , Schweller et al und Barbour et al belegen daneben, dass die Prozesse an der Oberfläche wie Evaporation und Transpiration sowie die oberflächennahen Schichten, z. B. Oberboden und Bankettmaterial , einen großen Einfluss auf den Wasserhaushalt von Straßendämmen haben.…”
Section: Introductionunclassified
“…Despite its shortcomings, Fayer and Gee (1997) Benson et al (2004) showed that VADOSE/W can predict water balance in a landfill cover system more accurately than UNSAT-H. Similar results were reported by Adu-wusu et al (2007) in their prediction of the water balance in Whistle Mine, Ontario. Another study by Song and Yanful (2008)…”
Section: Numerical Modellingmentioning
confidence: 79%
“…Capillary barrier has also been used in the mining industry (Woyshner and Yanful 1995;Yanful and Choo 1997;Cabral et al 2000;Adu-Wusu and Yanful 2006;Adu-Wusu et al 2007). The contrast between fine and coarse-grained layers of capillary barrier restricts water infiltration through the interface between fine and coarsegrained layers.…”
Section: Capillary Barrier Cover Systemmentioning
confidence: 99%